Hospital variation in missed nursing care - Kalisch, Beatrice J; Tschannen, Dana; Lee, Hyunhwa; Friese, Christopher R (American journal of medical quality, 2011)
Quality of nursing care across hospitals is variable, and this variation can result in poor patient outcomes. One aspect of quality nursing care is the amount of necessary care that is omitted. This article reports on the extent and type of nursing care missed and the reasons for missed care. The MISSCARE Survey was administered to nursing staff (n = 4086) who provide direct patient care in 10 acute care hospitals. Missed nursing care patterns as well as reasons for missing care (labor resources, material resources, and communication) were common across all hospitals. Job title (ie, registered nurse vs nursing assistant), shift worked, absenteeism, perceived staffing adequacy, and patient work loads were significantly associated with missed care. The data from this study can inform quality improvement efforts to reduce missed nursing care and promote favorable patient outcomes.